Analysis of the dynamics of Staphylococcus aureus binding to white blood cells using whole blood assay and geno-to-pheno mapping - Daria Gaidar; Alice Jonas; Ruslan Akulenko; Ulla Ruffing; Mathias Herrmann; Volkhard Helms; Lutz von Müller (Elsevier, 2020)
Given that binding and internalization of bacteria to host cells promotes infections and invasion, we aimed at characterizing how various S. aureus isolates adhere to and are internalized by different white blood cells. In particular, the role of genetic determinants on the association kinetics should be unveiled. A flow cytometric (FACS) whole blood assay with fluorescently labelled isolates was applied to 56 clinical S. aureus isolates. This phenotypic data was then linked to previously obtained genotyping data (334 genes) with the help of a redescription mining algorithm. Professional phagocytes showed a time-dependent increase of bacterial adhesion and internalization. Isolates showing higher affinity to granulocytes were associated with lower binding to monocytes. In contrast binding activity between S. aureus and lymphocytes could be subdivided into two phases. Preliminary binding (phase 1) was highest directly after co-incubation and was followed by S. aureus detachment or by sustained binding of a small lymphocyte subset (phase 2). Strain-dependent low granulocyte binding was observed for clonal complex 5 (CC5) isolates (MRSA), as compared to CC30 and CC45 (MSSA). S. aureus isolates associated with low granulocyte phagocytosis were characterized by the presence (cap8, can) and the absence (sasG, lukD, isdA, splA, setC) of specific hybridization signals.